Estudo de soroconversão com formulações da vacina Biken CAM-70 contra sarampo Comparison of seroconversion rates with CAM-70 measles vaccine at different dosages - Luiz Antonio B Camacho; Marcos Silva Freire; Anna MY Yamamura; Maria da Luz Leal; George Mann (Universidade de São Paulo, 2000)
OBJETIVO: Comparar a resposta sorológica induzida por formulações com diferentes concentrações de vírus da vacina contra sarampo da cepa Biken CAM-70. MÉTODOS: Crianças sadias de 9 a 18 meses de um centro de saúde do Rio de Janeiro, RJ, cujos responsáveis concordaram em participar, foram randomizadas em três grupos vacinados com concentrações de 5.000, 1.000 ou 200 CCID50 (50% Tissue Culture Infective Dose). Os participantes e o pessoal da pesquisa ignoravam o tipo de vacina administrado. A avaliação sorológica foi realizada pelo teste de redução em plaque de lise. Duas análises intermediárias dos dados foram programadas. RESULTADOS: Das 223 crianças recrutadas, 84% completaram todos os procedimentos; 79% tinham idade menor que 10 meses; e 93% não tinham anticorpos contra sarampo no soro pré-vacinal. As proporções de soroconversão (quadruplicação das concentrações pré-vacinais) foram 82%, 55% e 37% (p<0,0000), nos grupos vacinados com 5.000, 1.000 ou 200 CCID50, respectivamente. As diferenças nas concentrações médias de anticorpos pós-vacinais também foram substanciais e estatisticamente significativas (p<0,000). A soroconversão (independente da formulação da vacina) foi de 73% nas crianças com 10 ou mais meses de idade e 53% naquelas com menos de 10 meses. CONCLUSÕES: Formulações da vacina com concentrações inferiores a 5.000 CCID50 não induziram soroconversão satisfatória. O desempenho da vacina por faixas etárias foi compatível com o observado em outros estudos com a vacina Biken CAM-70 e indica que uma proporção apreciável de crianças vacinadas aos 9 meses pode não obter resposta imunológica plena. OBJECTIVES: To compare seroconversion rates induced by Biken CAM-70 measles vaccines at different viral concentrations. METHODS: Healthy children aged 9 to 18 months from a primary health care unit in Rio de Janeiro, Brazil, and whose guardians agreed with their participation, were randomly assigned to receive one of the following vaccine formulations: 5,000, 1,000 or 200 CCID50 (50% Tissue Culture Infective Dose). The research team, participants, and data analysts were blinded to the type of vaccine administered. Pre- and post-vaccination antibody levels were assessed through Plaque Reduction Neutralization Test. Two interim data analyses were planned to assess unequivocal evidence of the superiority of one of the vaccine types. RESULTS: From 223 recruited children, 84% completed the whole course. Of them, 79% were less than 10 months of age, and 93% did not show detectable measles antibodies in pre-vaccination serum. Seroconversion (four-fold increase in antibody levels) in groups vaccinated with 5,000, 1,000 or 200 CCID50, were 82%, 55%, and 37% (p<0.0000), respectively. Differences in the mean concentration of post-vaccination antibodies were also substantial and statistically significant (p<0.000). Seroconversion rates (pooling data from all vaccine formulations) were 73% to children aged 10 months or more, and 53% in those below 10 months. CONCLUSIONS: Vaccines with concentrations below 5,000 CCID50 did not produce satisfactory seroconversion rates. The vaccine performance by age was consistent with that seen in other studies using Biken CAM-70 strain in which a sizable proportion of 9-month-old children failed to achieve full immunological response.